Reservoir Modeling Workflow Derived from a Central Luconia Carbonate Build-up - OOI , PHEY CHEE (2018)
Heterogeneities at multiple scales influence hydrocarbon production from Miocene isolated carbonate build-ups in South East Asia. Digital modeling is a useful tool to represent plausible realizations of such heterogeneities to test their impact. Central Luconia carbonate build-ups are complex reservoirs in terms of stratigraphy, facies and pore architecture. Therefore, these geological heterogeneities change stratigraphically. The objective of this thesis is to elaborate on the use of alternative modeling strategies tailor-made for the geological heterogeneities that are observed at hierarchical scales of stratigraphic layers.